Prototype of Sales Information System Based on Educational Book Consultan Data and Senior Educational Book Consultant - Sri Kuswayati; Muchamad Rusdan (JUSTINFO | Jurnal Sistem Informasi dan Teknologi Informasi, 2023)
The purpose of this study is to provide a solution to the problem of the risk of loss of sales data and EBC personal data and the possibility of data duplication that results in incompatible data points for each EBC, faster data retrieval than before the manual becomes computerized, simplifies data processing and means for leaders to get real-time sales information. The study was conducted with a qualitative approach that emphasizes a deep understanding of a particular problem. This study chooses the type of research design with primary and secondary data. Primary data sources were obtained from observations on KudeStation. Secondary data sources were obtained from literature studies related to the research conducted. The system development method used is the prototype method. The results showed that the problem of the risk of losing sales data and EBC personal data can be solved by using data stored in the database. With the application information system, data search becomes faster than before (manual) compared to after computerized with the data search feature. They are simplifying data processing by creating a sales information system. Provide a means for leaders to get real-time sales information by selecting a web-based sales information system so that after hosting this sales information system, all data can be accessed from anywhere in real-time.